Stakeholders selection for interorganizational systems: a systematic approach - Ballejos, Luciana C. (2006)
Stakeholders identification is a critical task for successful software projects. In general, there are no methodologies that allow performing it in a systematic way. Besides, several facts must be analyzed when the project is carried out in a context formed by multiple organizations. The complexity of these environments makes the task extremely hard. To face these difficulties, stakeholders are defined and analyzed taking into account the characteristics of the interorganizational dimension. Also a methodology is proposed for carrying out their identification that allows systematically specifying all people, groups and organizations whose interests and needs are affected by the information system in all the involved dimensions.